Land girls. Series 3 [videorecording (DVD)] - Barber, Ian (Television director); Hughes, Steve; Ward, Sophie; Mafham, Dominic; Gemmell, Becci; Hizli, Seline; Broadbent, Lou (Distributed by BFS Entertainment & Multimedia, 2012)
Set in rural England during the Second World War, the highly popular, award-winning drama returns for a third five-part series and continues to follow the lives and loves of the Land Girls who are working the fields in the Women's Land Army.